PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER ( NHT ) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV A SDN 51 BALAI MAKAM - Duri, Rapika; Antosa, Zariul; Alpusari, Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract :The purpose of this research to increase Match product study 2015 – 2016. This subject are the students class sixth of 51 Balai Makam Elementary School Bengkali Regency. They are cousist 33 people.The value teachers activity has increase about four meeting so it’s to be good. The first meeting get 75% with good category the second meeting get 79,16% with good category . while in the second cycle in the first meeting teacher activity get 87,5 % with very good category in the second meeting get 95,83% with very good category. While the student activity in the first meeting get 58,33 % with bad category . in the firt cycle the second meeting the student activity get 66,7% with good category . next in the second cycle the first student activity get 75 % with good category in the second meeting get 87,5% with very good category. Whereas to increase the product of study student we can see from their value in each cycle . The foundation value is 65,75 % keep increasing in the first cyle become 68,51% it’s means upgrading 2,76 ( 4,19% ) from faundation value and the second cycle become 80,72%.Key Words : Model Pembelajaran Kooperatif tipe Numbereed Head Together,Product Study Mathematic